(untitled) (Eurasian Research Bulletin, 2022)
Medical support for rescue operations in emergency situations (ES) is a set of measures to preserve the life and health of the population and rescuers: medical evacuation measures (medical evacuation support), sanitary and anti-epidemic measures, measures of medical protection of the population and personnel involved in the liquidation of emergencies, supply of medical equipment.